A study on the signage system in Melaka, the UNESCO heritage sites - Abdul Rahim, Noor Roziana; Abdul Rahman, Julaila; Abdul Razak, Rajabi (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2019)
Despite of the massive tourist visit to Melaka UNESCO sites; the sites had been one of the most visited places in Malaysia in 2015. Melaka, as one of the important UNESCO heritage sites in Malaysia with many public facilities particularly heritage buildings truly needs to consider effective signage design application to make it easier for tourist way-finding. There has been a variety of research done about user experience and way-finding, but the studies have focused either on the effectiveness of signage design or user experience. However, there is very less study that explores the understanding in connection on tourist experience and signage in prominent areas. Therefore, the aim of this study was to explore the understanding in connection to tourist experience in UNESCO heritage sites by referring to the signage. The data was collected through the pilot survey and photo elicitation in the UNESCO sites of Melaka.The findings indicated that most of the signage in the heritage sites were not effective due to the unsuitable location and ineffective design of the signage. For the directional sign, most of the sign provide the directions within a site or building including arrows. However, usage of symbols in the directional signs are minimal. For information signs at the heritage sites are related to overall orientation within a site or building. Some of the information sign do not contain maps, diagrams and directory signs that able to give the detail information to the users because of the size is too small to fit all the information needed. Lastly for identification sign, due to some of the places are not directed by the directional signs, the tourist still unable to reach the desired sites although the sites have a good identification signage. In conclusion, it is suggested that the signage should be sensitively located, scaled and detailed so as not to obscure ambiguous or distract the integrity of the historical objects.